KONSEP KETATANEGARAAN ISLAM MENURUT AL-FARABI DAN AYATULLAH KHUMAENI - Abidin, Ahmad Zaenal (UIN Sunan Kalijaga Yogyakarta, 2012)
Discourse on whether Islam has a conception of the state system a topic that is always interesting to talk about. Basically constitutional Islamic political thought is divided into three periods, namely the classical period that lasted from the 7th century until the 13th century, a period that lasted from the mid-14th century until the 19th century, and the modern period that lasted from the 19th to the present. Al-Farabi was one of the first thinkers (classic) in the constitutional history of political Islam. He is the first Muslim political thinkers who seek confronts, tie, and then align the classical Greek political thought in Islam. On the other hand Ayatuallah Imam Khomaeni a thinker as well as political actors reperesentasi ketatanegraan Islam in the modern period. Imam Khomaeni is a major driving force of the revolution that occurred in 1979 in the State of the Mullahs of Iran. Al-Farabi in subdivision political theory asserts that the purpose of the establishment of the State is to achieve happiness. While Ayatollah Khomaeni constitutional political views politics as a business is achieving goals based on divine values or religious. Religion Islam is not separate from political life. because the State's duty is to uphold religion. That is why Islamic law to be the law of the State.